Effect of laser annealing on thermally evaporated CdTe thin films for photovoltaic absorber application. (October 2018) - Khan, N.A.; Rahman, K.S.; Aris, K.A.; Ali, A.M.; Misran, Halina; Akhtaruzzaman, M.; Tiong, S.K.; Amin, N.
Highlights: CdTe thin films were deposited by thermal evaporation method. Laser annealing was performed as the post deposition treatment. Nd:YAG laser in three different modes were used during the annealing process. CdTe crystallizes in cubic and hexagonal structure with (1 1 1) preferential orientation. Bandgap of CdTe thin films can be tailored from 1.44 eV to 1.66 eV. Abstract: CdTe thin films were deposited on soda lime glass substrates (SLG) by thermal evaporation technique under high vacuum condition. As-deposited CdTe thin films were subjected to post deposition laser annealing treatment at three laser output energies of 50, 60, and 70 J/pulse. Laser annealing was employed using the laser beam with combined wavelengths of 1064 nm and 532 nm, where the laser energy was varied and the oscillator frequency was kept fixed at 10 Hz. XRD was employed to find the structural properties of the as-deposited and laser annealed CdTe thin films. Topography and surface morphology of the CdTe thin films were investigated using AFM and FESEM, respectively. Chemical composition and stoichiometry of the films were analysed by EDX integrated with FESEM. Electrical properties of the CdTe films were measured using Hall Effect measurement system and the optical properties of the as-deposited and laser annealed CdTe films were studied by UV–Vis. XRD analysis showed that as-deposited and laser annealed CdTe thin films had a mixed phase of cubic and hexagonal structures with the preferential crystal orientation of C (1 1 1) at approximately 2θ = 23.80°. CdTe thin films laser annealed at 60 J/pulse had better crystalline property having minimum internal strain with lower surface roughness and larger grain size resulting in optimized coalescence. EDX, Hall Effect, and UV–Vis results for the film laser annealed at 60 J/pulse depicted good compositional stoichiometry, better electrical properties and optimum optical properties showing the prospects as a potential absorber for CdTe thin film solar cells.